The Making of Black Detroit in the Age of Henry Ford - Bates, Beth Tompkins (Book collections on Project MUSE., 2012)
In the 1920s, Henry Ford hired thousands of African American men for his open-shop system of auto manufacturing. This move was a rejection of the notion that better jobs were for white men only. This book explains how black Detroiters, newly arrived from the South, seized the economic opportunities offered by Ford in the hope of gaining greater economic security. As these workers came to realize that Ford's anti-union 'American Plan' did not allow them full access to the American Dream, their loyalty eroded, and they sought empowerment by pursuing a broad activist agenda.